2014
DOI: 10.3109/15622975.2014.909606
|View full text |Cite
|
Sign up to set email alerts
|

Central coherence in eating disorders: An updated systematic review and meta-analysis

Abstract: As well as supporting the results of previous studies by providing evidence of inefficient global processing, this review has provided evidence of superior local processing, which supports the WCC hypothesis in ED.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
165
2
7

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 184 publications
(183 citation statements)
references
References 41 publications
9
165
2
7
Order By: Relevance
“…Current evidence points to a strong role for three particular deficits, impaired theory of mind (Caglar-Nazali et al, 2014;Davis et al, 2016 ), weak central coherence (Lang et al, 2014), and deficits in executive functions, including problems in set-shifting (Roberts et al, 2007;Tchanturia et al, 2012;Westwood et al, 2016). Social interaction impairments and reciprocal communication deficits, which are key symptoms of ASD, have also been reported in ED patients (Wentz et al, 2009;Zucker et al, 2007).…”
Section: Autistic Traits In Clinical Eating Disordersmentioning
confidence: 99%
“…Current evidence points to a strong role for three particular deficits, impaired theory of mind (Caglar-Nazali et al, 2014;Davis et al, 2016 ), weak central coherence (Lang et al, 2014), and deficits in executive functions, including problems in set-shifting (Roberts et al, 2007;Tchanturia et al, 2012;Westwood et al, 2016). Social interaction impairments and reciprocal communication deficits, which are key symptoms of ASD, have also been reported in ED patients (Wentz et al, 2009;Zucker et al, 2007).…”
Section: Autistic Traits In Clinical Eating Disordersmentioning
confidence: 99%
“…Six studies employing samples of adults with AN demonstrated that adults with AN performed significantly less globally than those without AN (d=-0.56 (95% C.I. -0.76, 0.35), p<0.001 [5].…”
Section: Rey-osterrieth Complex Figure Test (Roft [12])mentioning
confidence: 99%
“…With limited effective treatment options for AN, research interests within the eating disorders field have recently turned to examining possible underlying factors and traits such as cognitive processing styles. This work has highlighted that adults with AN exhibit a specific neuropsychological profile with certain areas of weakness (relative to their IQ), that may help to maintain the disorder, namely that of inefficient set-shifting [2][3][4] and weak central coherence [5]. Weak central coherence refers to a cognitive processing style whereby there is a relative lack of gistful 'bigger picture' thinking alongside superior attention to detail [6].…”
Section: Introductionmentioning
confidence: 99%
“…Previous research has suggested a neurocognitive profile illustrating inefficiencies in cognitive flexibility, attention, central coherence, social cognition and long-term and visuospatial memory [6][7][8][9], but these neuropsychological processes are generally not addressed in treatment. Cognitive remediation therapy (CRT) aims to raise awareness of thinking styles and to improve strategies through series of exercises designed to develop a more flexible and global thinking style [6,9].…”
Section: Introductionmentioning
confidence: 99%
“…Cognitive remediation therapy (CRT) aims to raise awareness of thinking styles and to improve strategies through series of exercises designed to develop a more flexible and global thinking style [6,9]. CRT has been implemented in individual and group settings, both for outpatients and inpatients, with promising results (for review, see [10]).…”
Section: Introductionmentioning
confidence: 99%